MIDWIFERY CARE FOR A 4 -MONTH-OLD BABY IN JEUMPET VILLAGE, SUB-DISTRICT DARUL IMARAH, THE DISTRICT OF ACEH BESAR IN 2026: Midwifery Care For Children - Nayla NaJwa; Nurlaili Ramli; Fitriani Fitriani (Journal of Midwifery and Community Health (JMCH), 2026)
Background: Infancy is a crucial golden period in determining the quality of a child's growth and development. Optimal healthcare services during infancy are essential to support growth and development and prevent health problems that could impact quality of life in the future. This midwifery management aims to describe the implementation of midwifery care for 4-month-old Baby A in Jeumpet Village, Darul Imarah District, Aceh Besar Regency.Method: A descriptive case study was used, including history-taking, physical examination, growth and development assessment, and evaluation of the baby's basic needs.Result: The assessment results indicated that Baby A was in good general condition, was exclusively breastfed, had age-appropriate growth, and demonstrated developmental milestones for a 4-month-old. The baby was able to lift his head and chest in the prone position, reach for objects, and respond socially to his environment. In addition, the baby had received basic healthcare and immunizations according to the recommended schedule.Conclusion: The midwifery care provided focused on monitoring growth and development, supporting exclusive breastfeeding, providing health education to the family, and stimulating development appropriate to the baby's age. Comprehensive and continuous midwifery care plays an important role in maintaining infant health and supporting optimal growth and development.